Transcriptomic profiles of Mannheimia haemolytica planktonic and biofilm associated cells. - Hao Ma; David P Alt; Shollie M Falkenberg; Robert E Briggs; Fred M Tatum; Michael L Clawson; Eduardo Casas; Rohana P Dassanayake (PLoS ONE, 2024)
Mannheimia haemolytica is the principal agent contributing to bovine respiratory disease and can form biofilms with increased resistance to antibiotic treatment and host immune defenses. To investigate the molecular mechanisms underlying M. haemolytica biofilm formation, transcriptomic analyses were performed with mRNAs sequenced from planktonic and biofilm cultures of pathogenic serotypes 1 (St 1; strain D153) and St 6 (strain D174), and St 2 (strain D35). The three M. haemolytica serotypes were cultured in two different media, Roswell Park Memorial Institute (RPMI) 1640 and brain heart infusion (BHI) to form the biofilms. Transcriptomic analyses revealed that the functions of the differentially expressed genes (DEGs) in biofilm associated cells were not significantly affected by the two media. A total of 476 to 662 DEGs were identified between biofilm associated cells and planktonic cells cultured under BHI medium. Functional analysis of the DEGs indicated that those genes were significantly enriched in translation and many biosynthetic processes. There were 234 DEGs identified in St 1 and 6, but not in St 2. The functions of the DEGs included structural constituents of ribosomes, transmembrane proton transportation, proton channels, and proton-transporting ATP synthase. Potentially, some of the DEGs identified in this study provide insight into the design of new M. haemolytica vaccine candidates.